2016
DOI: 10.1016/j.jvs.2016.07.106
|View full text |Cite
|
Sign up to set email alerts
|

Technical options for treatment of in-stent restenosis after carotid artery stenting

Abstract: The available evidence for ISR treatment is still limited owing to methodologic heterogeneity; therefore, no recommendation on the optimal intervention can be provided. Although PTA is the common treatment for ISR, recurrent ISR seems to limit the durability, leading to recurrent interventions and cost implications. A uniform definition for ISR is needed with a standardized workup to compare the treatment options based on individual patient data analysis. Drug-eluting techniques are emerging and may become the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 53 publications
2
43
0
3
Order By: Relevance
“…This could explain the varying results seen across different case series of carotid ISR treated with the DEB. In an updated review by Pourier et al, 10 a total of 239 interventions were reported in 234 patients with carotid ISR. Recurrent carotid stenosis was observed in 47 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could explain the varying results seen across different case series of carotid ISR treated with the DEB. In an updated review by Pourier et al, 10 a total of 239 interventions were reported in 234 patients with carotid ISR. Recurrent carotid stenosis was observed in 47 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A written consent was obtained from both patients prior to the procedure. We used DEB for angioplasty as “off‐label use of FDA approved device” similar to cutting and scoring balloons for carotid ISR in previous studies 10 . Off‐label use is relatively common as companies do not seek U.S Food and Drug Administration (FDA) approval for neurovascular application for rare indications such as carotid artery ISR due to small market 26 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…До 2013 г. в мировой практике зарегистрировано лишь 39 пациентов, которым проведена КЭЭ с удалением стента из внутренней сонной артерии, и 200 больных, которым выполнено повторное эндоваскулярное лечение [5,6]. Частота инсульта По данным исследований, среднее время рецидивирующих симптомов после КАС составляет 6,5 мес.…”
Section: Discussionunclassified
“…(диапазон от 2 до 54 мес.) [4][5][6]. Чаще всего это пациенты пожилого возраста (средний возраст 67 лет), мужского пола, с выраженной коморбидной патологией [4][5][6].…”
Section: Discussionunclassified